Menyinergikan Keterlibatan Masyarakat dan Inovasi Berbasis AI:Strategi Fokus untuk Pertumbuhan Ekonomi Berkelanjutandari UMKM Cimol Bojot AA - Nabila Zulfa Azizah; Nurul Laily Oktaviana; Reihan Ahmad Nurhakim; Megha Sakova (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the influence of Community Engagement, AI-Based Innovation, and Focus Strategy on the Sustainable Economic Growth of UMKM Cimol Bojot AA, tested partially, in combination, and simultaneously. The study is grounded in the premise that community engagement and artificial intelligence-based innovation are strategic forces which, combined with an appropriate focus strategy, can drive sustainable economic growth in MSMEs. A quantitative associative approach was employed using purposive sampling with 36 respondents who were customers of UMKM Cimol Bojot AA. Data were collected through a five-point Likert-scale questionnaire and analyzed using validity and reliability tests, followed by path analysis in SPSS to test seven hypotheses (H1–H7). The results show that, tested individually, Community Engagement (Beta = 0.815), AI-Based Innovation (Beta = 0.564), and Focus Strategy (Beta = 0.912) each had a positive and significant effect on Sustainable Economic Growth. However, when tested in combination or simultaneously, only Focus Strategy remained significant, while the other two variables lost their significance, indicating an overlap of influence among the variables. These findings confirm that Focus Strategy is the most dominant factor driving the sustainable economic growth of UMKM Cimol Bojot AA, while Community Engagement and AI-Based Innovation act as supporting factors that operate through the focus strategy.